Data measurement system for non-destructive quality testing of hard alloys - I. K. Tsybrii; I. L. Vyalikov; V. I. Ignatenko (Advanced Engineering Research, 2018)
Introduction. It is known that the quality of products from sintered hardmetals, if the fabrication technique is not violated, is determined by the phase composition and an average grain size of the carbide phase. However, hard alloys have a disadvantage inherent in all products of powder metallurgy - the inhomogeneity of the structure and the corresponding variation of properties. Traditional methods of monitoring the structure and phase composition according to the results of selective destructive tests prevent from receiving quality data under the production conditions and do not guarantee the identity of the properties of all batch products under study. The major method of non-destructive quality control of hard alloys is coercimetry, but domestic coercimeters are currently not produced. In this regard, the work objective is to create a domestic data measurement system for non-destructive quality testing of hard alloys and an assessment of the reliability of the results obtained with its help.  Materials and Methods. Cylindrical and spherangular rods with the diameter of 4 to 10 mm, made of alloys of VK8 and VK10HOM grades, were used in the work. The method of comparison with a certified product was used to determine the coercitive force in the data measuring system. Research Results. The coercive force of two batches of products from hard alloys of VK10HOM and VK8 grades was measured using the developed data measuring system and KOERZIMAT 1.097 HcJ coersimeter. Discussion and Conclusions. The experimental studies show that the values of the coercitive force of the samples obtained on different equipment have approximately the same level. The inhomogeneity of the structure characteristic of sintered hardmetals being a fabrication technique effect is confirmed. Providing that the relative error of measuring the coercitive force for each sample should be within ± 6%, the results obtained can be considered satisfactory. It is shown that the measurement algorithm proposed and implemented in the data measurement system through comparing the characteristics of the tested and certified samples with the known coercitive force, allows the manufacturer of hard alloy products to expand the sample of inspected products up to 100%, and to significantly reduce the costs for non-destructive testing of products.